2019
DOI: 10.1038/s41598-019-49808-4
|View full text |Cite
|
Sign up to set email alerts
|

Tracking a mass mortality outbreak of pen shell Pinna nobilis populations: A collaborative effort of scientists and citizens

Abstract: A mass mortality event is devastating the populations of the endemic bivalve Pinna nobilis in the Mediterranean Sea from early autumn 2016. A newly described Haplosporidian endoparasite (Haplosporidium pinnae) is the most probable cause of this ecological catastrophe placing one of the largest bivalves of the world on the brink of extinction. As a pivotal step towards Pinna nobilis conservation, this contribution combines scientists and citizens’ data to address the fast- and vast-dispersion and prevalence out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 62 publications
3
111
0
Order By: Relevance
“…It has been previously indicated that corresponding sea currents could be involved in transporting pathogens and/or their still unknown vectors or fomites to promote disease dispersion [ 27 ]. Recent studies applied modelling of the sea currents directions and movement to P. nobilis MMEs [ 4 ]. The surveillance program designed to monitor MMEs in naïve areas of the Croatian coast took into account the major direction and speed of prevailing surface sea currents.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously indicated that corresponding sea currents could be involved in transporting pathogens and/or their still unknown vectors or fomites to promote disease dispersion [ 27 ]. Recent studies applied modelling of the sea currents directions and movement to P. nobilis MMEs [ 4 ]. The surveillance program designed to monitor MMEs in naïve areas of the Croatian coast took into account the major direction and speed of prevailing surface sea currents.…”
Section: Resultsmentioning
confidence: 99%
“…Protozoans are typically the first putative pathogens investigated in cases of mass mortality involving bivalves. In particular, haplosporidian endoparasites have been the cause of mortality events for many bivalve populations [ 45 ], and they have been extensively studied, especially in mollusks of high commercial interest [ 46 , 47 , 48 , 49 , 50 , 51 ]. Indeed, H. pinnae was initially considered as the potential promoter of the mass mortality of P. nobilis [ 7 , 8 ] because it was the first pathogen found in large quantities on dead and moribund fan mussel individuals [ 12 , 13 , 14 , 15 ] and because it has been considered to be a specific-species protozoan of P. nobilis .…”
Section: Discussionmentioning
confidence: 99%
“…A wasting disease (90% to near 100% mortality) occurred in Spain in 2016 (Darriba, 2017;Vázquez-Luis et al, 2017). Subsequently, this mortality spread to the whole of the Mediterranean (González-Wangüemert et al, 2018;Pergent, 2018;Bianchi et al, 2019;Cabanellas-Reboredo et al, 2019). Mortality is caused by a unicellular parasite, Haplosporidium pinnae, a species previously undescribed (Catanese et al, 2018).…”
Section: A Vector Of Diseases Of Metazoans Of Which the Extirpation Cmentioning
confidence: 99%
“…The latter hypothesis is by far the most probable: the new parasite presents many of the features that characterize an introduced species (see Ribera and Boudouresque, 1995;Boudouresque, 1999a), e.g., the weak genetic diversity and the pattern of expansion. Many haplosporidans are parasites of bivalves in the north-western Pacific; some of them were introduced to Europe via shellfish transfers, with dire consequences (Sindermann, 1992;Cabanellas-Reboredo et al, 2019). The possible primary vector species of H. pinnae (Magalana gigas?…”
Section: A Vector Of Diseases Of Metazoans Of Which the Extirpation Cmentioning
confidence: 99%
See 1 more Smart Citation